2018
DOI: 10.5853/jos.2017.01522
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid in Stroke Prevention in Countries without Mandatory Folic Acid Food Fortification: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background and PurposeAdditional folic acid (FA) treatment appears to have a neutral effect on reducing vascular risk in countries that mandate FA fortification of food (e.g., USA and Canada). However, it is uncertain whether FA therapy reduces stroke risk in countries without FA food fortification. The purpose of this study was to comprehensively evaluate the efficacy of FA therapy on stroke prevention in countries without FA food fortification. MethodsPubMed, EMBASE, and clinicaltrials.gov from January 1966 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 58 publications
0
31
0
4
Order By: Relevance
“…A recent systematic review identified 13 RCTs of folic acid therapy in which stroke was reported as an outcome and most participants (>50%) in a trial resided in countries without mandatory fortification of food with folic acid. 27 At total of 65 812 participants were enrolled in 13 trials; 12 trials included individuals with pre-existing conditions: stroke (one trial), coronary heart disease (five trials), cardiovascular disease (one trial), end-stage renal disease or advanced chronic kidney disease (three trials), hypertension (one trial) and oesophageal dysplasia (one trial), while one trial included individuals living in high altitude. Folic acid alone or the combination of folic acid and minimal cyanocobalamin (≤0.05 mg/day) was used in an active treatment group in eight trials, whereas the combination of folic acid and cyanocobalamin (≥0.4 mg/day) was used in an active treatment group in five trials.…”
Section: Evidence For Homocysteine As a Causal Risk Factor For Strokementioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review identified 13 RCTs of folic acid therapy in which stroke was reported as an outcome and most participants (>50%) in a trial resided in countries without mandatory fortification of food with folic acid. 27 At total of 65 812 participants were enrolled in 13 trials; 12 trials included individuals with pre-existing conditions: stroke (one trial), coronary heart disease (five trials), cardiovascular disease (one trial), end-stage renal disease or advanced chronic kidney disease (three trials), hypertension (one trial) and oesophageal dysplasia (one trial), while one trial included individuals living in high altitude. Folic acid alone or the combination of folic acid and minimal cyanocobalamin (≤0.05 mg/day) was used in an active treatment group in eight trials, whereas the combination of folic acid and cyanocobalamin (≥0.4 mg/day) was used in an active treatment group in five trials.…”
Section: Evidence For Homocysteine As a Causal Risk Factor For Strokementioning
confidence: 99%
“…A meta-analysis of these trials among people who were living in countries without mandatory folic acid fortification in food found that folic acid therapy was associated with a lower risk of any future stroke compared with control (RR 0.85, 95% CI 0.77 to 0.95; p=0.004; 3–8 fewer events per 1000 patients). 27 …”
Section: Evidence For Homocysteine As a Causal Risk Factor For Strokementioning
confidence: 99%
See 2 more Smart Citations
“…Higher levels of Hcy (i.e., HHcy) have been shown to affect methylation potential and DNA methylation, while in vitro acute treatment of lymphocytes from healthy male donors with HHcy (i.e., >20 mol/L for 8 h) failed to cause any noticeable change(s) in the methylation or DNA hypomethylation, indicating that HHcyinduced toxicity is most likely the result of a chronic, rather than acute, response (Fux et al 2005). Recent studies have shown that folate supplementation alone does not reduce the risk(s) of coronary artery disease and stroke (Banerjee et al 2007;Gao et al 2012;Hsu et al 2018;Yu et al 2011). Several clinical studies revealed that Hcy levels to be significantly higher in multiple sclerosis patients than in control individuals without B 12 and (or) folate deficiency, in the absence of MTHFR mutation (Ho et al 2002;Kararizou et al 2013;Kruman et al 2000;Teunissen et al 2008).…”
Section: Genetic Determinant Of Hhcymentioning
confidence: 99%